Menggalang Potensi Budaya Lokal untuk Mengangkat Bargaining Position Masyarakat: Memetik Hikmah Pemetaan Partisipatif di Gunungkidul - JSE Yuwono; Uji Nugroho Winardi (Bakti Budaya: Jurnal Pengabdian kepada Masyarakat, 2018)
The district of Gunungkidul was chosen as a potential area for the adoption of a new approach in Community Engagement (CE) program. Participatory mapping, reinforced by the application of the Geographic Information System (GIS) as a new approach, became a breakthrough amid the vastness of humanities, which still seems to be fragmented in each study program. Terefore, a platform is neended to optimize the potential of FIB UGM to address the diversity of cultural aspects in a community. Tis CE is designed to empower both parties at once, ie community and college. For the community, recollecting of their cultural properties can be a powerful capital for potential development with a structured and accessible database. Tis cultural richness helps them to initiate and implement the sustainable village development programs. Strengthening and developing their identity and integrity of local culture can be achieved if their overall potential can be mapped. For the college, CE becomes a model that can provide more mature readiness in actualizing its “tri dharma”, either through the preparation of human resources and methodological reinforcement.